Analysis of Language Politeness of Local Party Legislative Candidates in Aceh Jaya - munawar, munawar; Yusuf, Yusri; Ramli, Ramli (East Asian Journal of Multidisciplinary Research, 2024)
This study examines the linguistic politeness of local party candidates in Aceh Jaya during the 2023-2024 general election campaign period. Using a qualitative descriptive method, the research analyzes the politeness of language based on data collected from candidates through observation, recording, and documentation. The analysis follows Geoffrey's politeness principles, which include the maxims of tact, generosity, praise, modesty, agreement, and sympathy. The findings reveal that most candidates adhere to these linguistic politeness principles.